PENGGUNAAN STARTER REBAR DENGAN CHEMICAL EPOXY PADA REKONSTRUKSI DINDING PENAHAN TANAH CANTILEVER - Valentana Ardian Tarigan; Immanuel Panusunan Tua Panggabean (Universitas Quality, 2019)
The construction of cantilever retaining wall uses reinforcement as part of the retaining wall’ structure. Reinforcement of the construction of the Retaining Wall is carried out on construction if there is a need for additional reinforcement on the structure or carrying out reconstruction on the structure of the retaining wall. Research on the use of starter rebar uses chemical epoxy, which is used to reconstruct the retaining walls. Soil investigation is carried out because the soil in this structure acts as a load, then this soil parameter is calculated as a lateral force on the wall that makes the rolling moment, and sliding. The land load also acts as a counter weight behind the wall. The study of the use of back reinforcement on the structure of cantilever type retaining wall uses D19-170 as the main reinforcement in the tensile area and D16-170 in the compressed area. Reinforcement for used D13-170.